Implementing Suicide Risk Screening in Pediatric Medical Patients: Feasible Quality Improvement Projects that Can Save Lives. Issue 3 (3rd July 2021) - Mournet, Annabelle M.; Horowitz, Lisa M.
ABSTRACT: With rising youth suicide rates in the US and around the world, medical settings have been leveraged as partners in prevention. Suicide risk screening programs can detect youth who may otherwise pass through the health care setting with unrecognized suicide risk. Outpatient primary care clinics and inpatient medical units are well positioned to intervene to address this critical public health crisis. Through the use of the Plan-Do-Study-Act quality improvement framework, suicide risk screening can be efficiently and effectively implemented in medical settings to identify suicide risk among youth, without overburdening busy healthcare systems.